STUDI LITERATUR CORAK PENAFSIRAN AL-QUR’AN: KASUS TAFSIR AL-MUNIR - Fisa, Triansyah; Usman, Zulkifli Abdurrahman; Faisal, Muhammad (Prodi Ilmu Al-Qur'an dan Tafsir, 2022)
This article discusses the development of the study of the interpretation of the Qur'an. The pattern of interpretation of the Qur'an in several universities is one of the topics discussed in lectures. The data in this article were collected from library sources which were then reduced and analyzed using a qualitative descriptive method and using a study approach to the interpretation of the Qur'an. This article finds that the study of the pattern of interpretation of the Qur'an conducted by scholars does not show significant developments. The study of interpretive styles tends to be repetitive and boring because scholars do not expand the object of interpretation being studied.